Experimental investigation of fatigue in a cantilever energy harvesting beam - Avvari, Panduranga Vittal (2018)
Over the last decade, cantilever energy harvesters gained immense popularity owing to the simplicity of the design and piezoelectric energy harvesting (PEH) using the cantilever design has undergone considerable evolution. The major drawback of a vibrating cantilever beam is its vulnerability to fatigue over a period of time. This article brings forth an experimental investigation into the phenomenon of fatigue of a PEH cantilever beam. As there has been very little literature reported in this area, an effort has been made to scrutinize the damage due to fatigue in a linear vibrating cantilever PEH beam consisting of an aluminum substrate with a piezoelectric macro-fiber composite (MFC) patch attached near the root of the beam and a tip mass attached to the beam. The beam was subjected to transverse vibrations and the behavior of the open circuit voltage was recorded with passing time. Moreover, electro-mechanical admittance readings were obtained periodically using the same MFC patch as a Structural health monitoring (SHM) sensor to assess the health of the PEH beam. The results show that with passing time the PEH beam underwent fatigue in both the substrate and MFC, which is observed in a complimentary trend in the voltage and admittance readings. The claim is further supported using the variation of root mean square deviation (RMSD) of the real part of admittance (conductance) readings. Thus, this study concludes that the fatigue issue should be addressed in the design of PEH for long term vibration energy harvesting.